FEATURES OF HEART LESIONS IN PATIENTS WITH VIRAL LIVER CIRRHOSIS - M. V. Chistyakova; A. V. Govorin (Столичная издательская компания, 2018)
Aim. To study the structural and functional parameters of the heart, as well as the effect of antiviral therapy on certain cardiohemodynamic parameters in patients with viral liver cirrhosis (VLC).Material and methods. 96 patients with VLC (median age 42.1 [36;44] years, median duration of the disease - 3.5 [2.8;6.7] years) were examined. Patients without ascites (n=59) were included into the 1st group, and patients with ascites (n=37) - into the 2nd group. The control group included 21 healthy volunteers. Standard and tissue echocardiography, Holter monitoring of electrocardiogram were performed in all participants.Results. Ventricular extrasystoles (class I to IVB) were found in 8 (13%) patients of the 1st group and in 12 (33%) patients in the 2nd group. The corrected interval of QT in the patients of the 1st group was 457.9 [442;468] msec, in the second group - 478 [433;502] msec, in control - 427.9 [406;438] msec (p<0.001). Supraventricular arrhythmias were represented by supraventricular extrasystoles in 15 (25%) patients of the 1st group and 18 (50%) - of the 2nd group; paroxysmal atrial fibrillation in 2 (3%) and 7 (19%) patients, respectively. The systolic velocity Sm of the lateral wall (3, 9 segments) in patients with ascites was lower by 23% and 25%, respectively, compared with the patients of the 1st group; Tei index increased in patients with ascites compared with the control group and the 1st group, p<0.001. In patients with VLC without ascites, the parameters characterizing the mass of the myocardium of the left ventricle increased, the left atrium and pulmonary artery widened. These disorders increased in patients with ascites; besides the systolic pressure in the pulmonary artery increased, and segmental and global systolic function of the left ventricle decreased. Antiviral therapy was accompanied by a decrease in the mass of the left ventricular myocardium, the index of left atrial volume and systolic pressure in the pulmonary artery.Сonclusion. The increase in the myocardium mass of left ventricle, left atrium, pulmonary artery diameter, as well as cardiac arrhythmia and prolongation of the corrected QT interval were found in patients with VLC without ascites. These changes were more pronounced in patients with ascites, and additionally they increased pressure in the pulmonary artery and decreased systolic function of the ventricles of the heart. The antiviral therapy had a positive effect on some cardiohemodynamic parameters.